Compassion training in healthcare: what are patients' perspectives on training healthcare providers?. Issue 1 (December 2016) - Sinclair, Shane; Torres, Mia-Bernadine; Raffin-Bouchal, Shelley; Hack, Thomas; McClement, Susan; Hagen, Neil; Chochinov, Harvey
Abstract Background The purpose of this qualitative study was to investigate advanced cancer patients' perspectives on the importance, feasibility, teaching methods, and issues associated with training healthcare providers in compassionate care. Methods This study utilized grounded theory, a qualitative research method, to develop an empirical understanding of compassion education rooted in direct patient reports. Audio-recorded semi-structured interviews were conducted to obtain an in-depth understanding of compassion training from the perspectives of hospitalized advanced cancer patients (n  = 53). Data were analyzed in accordance with grounded theory to determine the key elements of the underlying theory. Results Three overarching categories and associated themes emerged from the data: compassion aptitude, cultivating compassion, and training methods. Participants spoke of compassion as an innate quality embedded in the character of learners prior to their healthcare training, which could be nurtured through experiential learning and reflective practices. Patients felt that the innate qualities that learners possessed at baseline were further fashioned by personal and practice experiences, and vocational motivators. Participants also provided recommendations for compassion training, including developing an interpersonal relationship with patients, seeing the patient as a person, and developing a human connection. Teaching methods that patients suggested in compassion training included patient-centered communication, self-reflection exercises, and compassionate role modeling. Conclusions This study provides insight on compassion training for both current and future healthcare providers, from the perspectives of the end recipients of healthcare provider training – patients. Developing a theoretical base for patient centred, evidence-informed, compassion training is a crucial initial step toward the further development of this core healthcare competency.